Transcranial alternating current stimulation in affecting cognitive impairment in psychiatric disorders: a review - Biačková, Nina; Adamová, Andrea; Klírová, Monika (European archives of psychiatry and clinical neuroscience, 2024)
Transcranial alternating current stimulation (tACS) is a non-invasive brain stimulation method that, through its manipulation of endogenous oscillations, can affect cognition in healthy adults. Given the fact that both endogenous oscillations and cognition are impaired in various psychiatric diagnoses, tACS might represent a suitable intervention. We conducted a search of Pubmed and Web of Science databases and reviewed 27 studies where tACS is used in psychiatric diagnoses and cognition change is evaluated. TACS is a safe and well-tolerated intervention method, suitable for multiple-sessions protocols. It can be administered at home, individualized according to the patient''s anatomical and functional characteristics, or used as a marker of disease progression. The results are varying across diagnoses and applied protocols, with some protocols showing a long-term effect. However, the overall number of studies is small with a great variety of diagnoses and tACS parameters, such as electrode montage or used frequency. Precise mechanisms of tACS interaction with pathophysiological processes are only partially described and need further research. Currently, tACS seems to be a feasible method to alleviate cognitive impairment in psychiatric patients; however, a more robust confirmation of efficacy of potential protocols is needed to introduce it into clinical practise.
Keywords: Transcranial Direct Current Stimulation; Humans; SUD; Transcranial alternating current stimulation (tACS); Cognitive Dysfunction; COVID-19; přímá transkraniální stimulace mozku; ADHD; Psychiatry; Schizophrenia; Dementia; kognitivní dysfunkce; Mental Disorders; OCD; Cognitive impairment; Depression; Non-invasive brain stimulation (NIBS); duševní poruchy; lidé